(3GdfXQjI GdYGeI ddGcQGg ai GdbGfhf GdLfGFi (B: s (3OQGSI ebGQfI (B/ s - (3MSjf aJMi YWjI GMeOs; (3ahRjI YHOGdSJGQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3YQV GdHGMK ai gPg GdOQGSI ehVhY GdfXQjI GdYGeI ddGcQGg ai GdbGfhf GdLfGFi hCTGQ ai ebOeI GdHMK dSHH JfGhdg dgPG GdehVhY hcGf efgGLg gh GdefgL GdebGQf ajeG Hjf GdbGfhf GdhVYi heGjbGHdg ai GdTQjYI GdGSdGejI hPdc ddhbha Ydi fbGW GdGdJbGA hGdGNJdGa Hjf GdfXGejf hGTJedJ GdOQGSI Ydi HGHjf SHbgeG HGH JegjOis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B432-468s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdGcQGgs; (3GdXQha GdeTOOIs; (3GdfXQjI GdYGeIs; (3MGdI GdVQhQIs; (3TQhW GdNWQs; (3GQcGf GdLQjeIs; (3GdeSFhdjI GdLfGFjIs; (3GdGSJOdGds; (3eCehQ GdVHWs; (3GdGSJLhGHs; (3GdGYJQGas; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs